A Medal for Benny Movie Still - Paramount Pictures:::Creator::::::::::::
Charlie Martin (J. Carrol Naish) standing with dignitaries near his home in Slough Town just before receiving the Congressional Medal of Honor in his son's stead in Paramount Pictures 1945 production on 'A Medal for Benny.' From left in foreground: Charlie Martin, Governor of California (Edward Fielding), Mayor of Pantera (Grant Mitchell), Lolita Sierra (Dorothy Lamour). This exact shot not in movie.